1987
DOI: 10.1139/m87-085
|View full text |Cite
|
Sign up to set email alerts
|

Azospirillum effects on susceptibility to Rhizobium nodulation and on nitrogen fixation of several forage legumes

Abstract: Azospirillum brasilense Cd cell concentration of 105–107 colony-forming units (cfu)/mL applied 24 h before Rhizobium (106 cfu/mL), increased nodule formation in the non root hair zone, more than twofold, in pouch-grown Medicagopolymorpha and Macroptilium atropurpureum seedlings, compared with Rhizobium alone. The increase in nodule formation in pouch-grown Trifolium alexandrinum following preinoculation with Azospirillum was 20%. The percentage of nodulated seedlings rose from 0 to 25% when Medicago polymorpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The cell density of the bacteria applied as inocula has been also described as a factor involved in the nature of the effects observed in coinoculated legumes (Plazinsky and Rolfe, 1985;Yahalom et al, 1987). We have previously reported enhancement of R. leguminosarum bv.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The cell density of the bacteria applied as inocula has been also described as a factor involved in the nature of the effects observed in coinoculated legumes (Plazinsky and Rolfe, 1985;Yahalom et al, 1987). We have previously reported enhancement of R. leguminosarum bv.…”
Section: Discussionmentioning
confidence: 94%
“…Many papers have reported enhancement of nodulation and growth of a wide variety of forage and grain legumes, due to a positive interaction between Rhizobium species and diazotrophic soil bacteria of the genus Azospirillum (Iruthayathas et al, 1983;Plazinsky and Rolfe, 1985;Sarig et al, 1986;Yahalom et al, 1987;del Gallo and Fabbri, 1991). Azotobacter (particularly A. chroococcum) occurs widely in agricultural soils of temperate regions with almost neutral pH, and can be easily found in association with cereal and legume rhizospheres (Kole et al, 1988;Martõ Ânez-Toledo et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the effects of these bacteria on the nodulation process and biological nitrogen fixation. Some studies indicated that co-inoculation of Bradyrhizobium and certain PGPRs can positively affect symbiotic nitrogen fixation by enhancing both root nodule number or mass [25,26] and increasing the nitrogenase activity [27]. The co-inoculation of PGPRs with Bradyrhizobium increased the nodulation and nitrogen fixation in Glycine max at a low root zone temperature [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Azospirilla species are being used as seed inoculants under field conditions for more than a decade (Dobbelaere et al, 2001;Puente et al, 2009). The positive effect of Azospirillum in the nodulation and nitrogen fixation by rhizobia on several forage legumes was early reported (Yahalom et al, 1987). Since then, many works have been done and mostly are summarized in Bashan et al (2004).…”
Section: Getting More From Legumesmentioning
confidence: 99%